Main Directions of Image Processing. Creation of Digital Images (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
The rapid development of modern medicine requires close interaction with related fields: mathematics, physics, chemistry. One of these interactions is the processing and analysis of medical images. Images of the anatomical, histological structure and functions of the human body are the basis of medical science. Diagnosis, treatment and management of diseases are based on information obtained through medical imaging. In the process of digital image processing, the process of evaluating and filtering image quality indicators is of great importance. This article discusses the very important role of medical images in medicine, and in addition, their use as an auxiliary indicator for doctors in making an accurate diagnosis of patients.